StaTips Part VII: Anatomy of a Boxplot - Perinetti, Giuseppe (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Often researchers have the need to show graphically the behaviour of ordinal data or continuous data with great asymmetrical distribution. In all of these situations, a boxplot may be an appropriate way of data presentation. Because of its non-parametric nature, this kind of diagram is particularly useful when dealing with asymmetrical distribution. The different components of the most common variant of boxplot are herein detailed.